Programas disciplinares da Ciência da Informação: conformação do campo epistemológico no Brasil - Melo, Maytê Luanna Dias de (2017)
The study establishes a disciplinary design of Information Science through the elements that make up the disciplinary programs of the field in Brazil. To do this, we sought to explore the production that addresses the disciplinary elements, to characterize the context of institutionalization of these elements, to understand the constitutive nature and to show the contours of the disciplinary programs of the area. For that, we opted for the research of QualiQuantitative, approach through a bibliographical and documentary survey. The data were collected in the Sucupira Platform for the Post-Graduate Programs in the area of Information Science and Librarianship. It was also used the Laboratory of Intellectual Technologies and the Platform of Scientific Periodicals. All the data collected were systematized in tables and illustrations, then analyzed and discussed in consonance with the articles that composed the theoretical reference. The result indicates that the disciplinary programs promote disciplinary constructions identifying, based on the object of study of the area, the information. Its use, its practices, its processes, are essential to establish the attributions, to favor connections, to spread techniques among all the areas that are related to the Information Science. This was perceived in the scope of postgraduate programs through the areas of concentration, the training of the research faculty, the funding of research, associations and the focus and scope of scientific journals.